Daily Routine activity patterns and Status Offending among South Korean Youth: A Test of Hawdon's Reconceptualization of Involvement. (January 2019) - Lee, Wanhee; Garcia, Venessa
Abstract: The purpose of this study was to examine how routine activity patterns affect status offending among young boys and girls. Using path analysis, Hirschi's involvement concept, reconceptualized by Hawdon, was applied to the nationally representative Korean Children and Youth Panel Survey (KCYPS) data of 2280 adolescents in South Korea. Results of path analyses demonstrated that daily routine was significantly different for boys and girls, and participation in activities with low visibility and instrumentality influenced status offending. In other words, the more time spent in a low visible space and noninstrumental routine patterns, the more likely it was to affect status offending. Therefore, if we understand the life patterns according to gender, strengthen visibility and instrumentality, and provide various policy alternatives accordingly, it will be possible to reduce status offending further. Theoretical relevance and limitations are discussed. Highlights: The purpose of this study was to examine how routine activity patterns affect status offending among young boys and girls. Using path analysis, Hirschi's involvement concept was applied to Korean Children and Youth Panel Survey. The more time spent in a low visible and noninstrumental daily routine, the more likely it was to affect status offending.